Analisa Prinsip Good Corporate Governance (GCG) Terhadap Implementasi Corporate Social Responsibility Pada PT. Pos Indonesia Regional VI Semarang - Aulia Arma; Sopi Sopi (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract Since the issuance of the regulation, every company is required to distribute part of its profits back to the community, which is known as the CSR Program. CSR is one of the company's responsibilities to society. The community directly or indirectly, a little or a lot, sooner or later will be affected by the company's activities. So that the community is slightly entitled to the company's profits. The implementation of CSR programs must be managed effectively and efficiently, for that it is important to monitor and evaluate the implementation of GCG principles in the implementation of CSR programs. This research is a quantitative descriptive study that aims to determine the application of the principles of Good Corporate Governance (GCG) in the implementation of the Corporate Social Responsibility (CSR) program at PT. Pos Indonesia (Persero) Regional VI Semarang. Data was collected through interviews, questionnaires, and documentation. Respondents in distributing the questionnaires were community beneficiaries of the 2019-2020 Partnership and Community Development Program. Data analysis used descriptive analysis, to calculate the index value. The results show that the principles of transparency, accountability, responsibility, independence, fairness/fairness have been applied in the CSR program of PT. Pos Indonesia (Persero) Regional VI Semarang. However, there are still shortcomings in the implementation of the principles of accountability and independence. The CSR program has been implemented well, but its distribution is still not optimal.